China in the World Culture, Politics, and World Vision - Wang, Ban (Sinotheory, 2022)
Ban Wang traces the shifting concept of the Chinese state from the late nineteenth century to the present, showing how the Confucian notion of tianxia-"all under heaven"-influences China's dedication to contributing to and exchanging with a common world.